2016
DOI: 10.1177/0042098016678341
|View full text |Cite
|
Sign up to set email alerts
|

Los Angeles employment concentration in the 21st century

Abstract: This paper is an empirical analysis of employment centers in the Los Angeles region from 1997-2014. Most extant work on employment centers focuses on identification methodology or their dynamics during a period of industrial restructuring from 1980-2000. This timely study examines hypotheses derived from more recent perspectives on urban concentration and dispersion including New Urbanism, Smart Growth, sustainable cities, and the recent Global Financial Crisis. We use point-based, rather than census tractbase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 52 publications
4
44
0
3
Order By: Relevance
“…His argumentation is based on the fact that the contemporary economy is not purely divided into agglomerations (place) and networks (space) but consists also of enclaves of export processing zones and arenas of trade fairs – which are labelled interplaces. Other concepts about polycentrism (Burger & Meijers ; van Meeteren et al ; Rauhut ), Edge Cities (Garreau ) or New economic sub‐centres (Krehl ; Kane et al ) see urban regions as economic and social entities in which processes of concentration and deconcentration take place.…”
Section: Resultsmentioning
confidence: 99%
“…His argumentation is based on the fact that the contemporary economy is not purely divided into agglomerations (place) and networks (space) but consists also of enclaves of export processing zones and arenas of trade fairs – which are labelled interplaces. Other concepts about polycentrism (Burger & Meijers ; van Meeteren et al ; Rauhut ), Edge Cities (Garreau ) or New economic sub‐centres (Krehl ; Kane et al ) see urban regions as economic and social entities in which processes of concentration and deconcentration take place.…”
Section: Resultsmentioning
confidence: 99%
“…Redfearn (2009) also documented the medium- and longer-term stability of the location of employment centres in Los Angeles. In a more recent study, Kane et al (2018) analysed the changes in employment centres in Los Angeles from 1997 to 2014 using more sophisticated data and methods, and found that despite a small proportion of total employment in centres, growth in centres outpaced overall employment growth in the region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Irvine Company maintains exceptionally tight control over zoning and land-use regulations, and the street networks consist largely of winding, high-speed arterial roads with residential communities set between them. While its business subcenter nearly rivals downtown Los Angeles for regional dominance (Kane et al, 2016), it is a rare example of being entirely synthetic in that its location has no historical precedent (Forstall and Greene, 1997).…”
Section: Study Areamentioning
confidence: 99%